Analisis dan Perancangan Sistem Informasi Customer Relationship Management (CRM) berbasis Web pada Sekolah Dasar Islam Terpadu (SDIT) Al Muthmainnah - Suroto, Suroto; Mulyono, Herry (LPPM Universitas Dinamika Bangsa, 2019)
The current form of customer relationship at the Sekolah Dasar Islam Terpadu (SDIT) Al Muthmainnah has not optimallyheld interaction with customers, therefore the SDIT Al Muthmainnah requires a Customer Relationship Management(CRM) system. This research aims to analyze and design a web-based CRM at SDIT Al Muthmainnah. With the SystemDevelopment Life Cycle (SDLC) method, this research only discusses the first 3 stages of SDLC; system investigation,system analysis, and system design. The design of the CRM model used is the Strategic Framework for CRM. Thesystem of modeling sets used is UML (Unified Modeling Language). The result of this research is prototype of webbased CRM at SDIT Al Muthmainnah that can improves the quality of customer relationships. This research can befurther developed into a mobile-based CRM system, integrated with the Sistem Informasi Akademik (SIAKAD), andmake adjustments to the level of education other than elementary school.